JURIDICAL REVIEW OF THE VALUE OF LEGAL CERTAINTY AND THE VALUE OF JUSTICE FOR THE MISUSE OF CLASS I NARCOTICS IN COURT DECISION NUMBER 304/PID.SUS/2020/PT SMG. - Setiawati, Sri; Hartati, Sri; Rubiyanto, Rubiyanto (UNTAG Law Review, 2024)
Legal certainty for narcotics abusers in Law Number 35 of 2009 concerning Narcotics does not yet have legal certainty where in practice abusers are often charged and even terminated by Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics which is without rights and against the law depositor, owner, who controls narcotics class I non-plants. Based on the description above, the author is interested in studying this scientific paper with the title Juridical Review of the Value of Legal Certainty and the Value of Justice for the Abuse of Narcotics Group I in conviction Number 304/PID.SUS/2020/PT SMG. In practice narcotics abusers still use Article 112 paragraph (1) of Law Number 35 of 2009 concerning Narcotics which is without rights and against the law of the depositor, the owner, who controls narcotics class I not plants even though there is a Supreme Court Circular Letter (SEMA) Number 3 of 2015 to identify the accused as an abuser. In its implementation, there are obstacles that exist in the authority of law enforcers, especially judges. This research also found that restorative justice for narcotics abusers by the courts is still not effective which is contained in the Appendix to the Decree of the Director General of the General Judiciary Agency Number 1691/DJU/SK/PS.00/12/2020 concerning Enforcement of the Guidelines for the Application of Restorative Justice in the guidelines for the application of restorative justice in the General Court environment as an effort that can be made in deciding cases of class I narcotics abuse.